The Influence of Language Policy on Foreign Language Learning in Secondary Schools: A Psycholinguistic Approach - Azizeh, Nur; Ismawati (CV. Goresan Pena, 2023)
The problem in this study is the lack of understanding of how language policies implemented in secondary schools can influence students’ motivation and performance in foreign language learning and the role of social and cultural aspects in the learning process. This study aims to examine the impact of language policy on students’ motivation, performance, and comprehension, considering a psycholinguistic approach and the influence of both local and global cultures. This study employs a literature review method, analyzing various relevant previous studies. The findings indicate that language policies integrating cultural elements and communicative approaches can enhance students’ motivation, improve their performance in language exams, and deepen their understanding of the learned language. Policies that consider social and cultural aspects contribute positively to students’ emotional connection with the foreign language and enhance their communication skills.